2009
DOI: 10.1136/jech.2008.085548
|View full text |Cite
|
Sign up to set email alerts
|

Job stressors and long-term sick leave due to depressive disorders among Japanese male employees: findings from the Japan Work Stress and Health Cohort study

Abstract: Job control and role ambiguity may be important predictors of long-term sick leave due to depressive disorders among male employees, independent of depressive symptoms and neuroticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 51 publications
(51 reference statements)
1
38
1
6
Order By: Relevance
“…Our finding that a one unit increase in job control was independently associated with a decreased risk of DP due to mental diagnoses confirms earlier studies (11)(12)(13)(14)(15)(16)(17)(18)(19)51). However, the results that each one unit increase, rather than a decrease, in job demands or social support predict a higher risk of DP contradict those of previous findings (13,17,31,52).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our finding that a one unit increase in job control was independently associated with a decreased risk of DP due to mental diagnoses confirms earlier studies (11)(12)(13)(14)(15)(16)(17)(18)(19)51). However, the results that each one unit increase, rather than a decrease, in job demands or social support predict a higher risk of DP contradict those of previous findings (13,17,31,52).…”
Section: Discussioncontrasting
confidence: 56%
“…One explanation for these contradictory results may be the application of a validated JEM (20)(21)(22), while the majority of other studies (11,(15)(16)(17)(18)(19) used individually reported data on experiences of such exposures. Also, previous studies have mainly studied these working conditions as categorical (median split, quartiles) rather than as continuous variables and have, therefore, only been able to capture variation within the different categories (11,(15)(16)(17)(18)(19)47). Another explanation is that since the information about psychosocial working conditions was based on sector-based occupations, adjusting for occupation to account for the influence of socioeconomic status was not possible.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neuroticism, which is one of the Big Five personality traits Costa [39], was associated with job stress and mental diseases. In a Cox's proportional hazard model analysis of the incidence of long-term sick leave because of depressive disorders, higher-level education, higher neuroticism, and having a white-collar job were associated significantly with sick leave because of depressive disorders [40]. Tokuyama [41] reported that the first onset of depression was associated with a past history of neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al [40] reported that low job control might be a strong predictor of longterm sick leave because of depressive disorders. In a review of the evidence, Glass and McKnight concluded the job uncontrollability contributed to negative psychological states largely when there was a discrepancy between career aspirations and occupational achievement.…”
Section: Discussionmentioning
confidence: 99%